Expression of beta glucosidase mined from metagenomic DNA data of bacteria in Vietnamese goats’ rumen in \(Escherichia coli\) system - Thi Quy, Nguyen; Thi Huyen, Do; Khanh Linh, Nguyen Thi; Hong Duong, Nguyen; Nam Hai, Truong (Academia Journal of Biology, 2022)
Screening and expression of new β-glucosidase genes (bgc) have attracted much attention because of their valuable application in a wide range of industrial areas such as bioethanol production, food and animal feed processing, paper making, and biotechnological processes. Previously, we mined a new bgc gene coding for its mature enzyme (BGC) from metagenomic DNA data of bacteria in Vietnamese goats’ rumen. Based on the NCBI database, the BGC sequence was found to be the highest similarity with β-glucosidase of Bacteroidales bacterium (60.52%). The BGC enzyme was previously annotated to have two domains GH3 and GH31 and highly expressed in E. coli. The aim of this work was to experimentally confirm the predicted gene by expressing and assessing the activity of recombinant BGC from E. coli strains of BL21, Rosetta 1, C43, and SoluBL21. Furthermore, the expression level and solubility of the BGC were also investigated by varying fermentation conditions such as temperature, medium components, and IPTG concentration. The activity of the crude enzyme was identified through substrates including esculin and p-Nitrophenyl-β-D-glucopyranoside (pNPG). The new BGC could be used as potential material for further enzyme characterization.